2006
DOI: 10.1074/jbc.m507804200
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of the Osterix (Osx, Sp7) Promoter by Tumor Necrosis Factor Identifies Disparate Effects of Mitogen-activated Protein Kinase and NFκB Pathways

Abstract: Osteoblast (OB) differentiation is suppressed by tumor necrosis factor-␣ (TNF-␣), an inflammatory stimulus that is elevated in arthritis and menopause. Because OB differentiation requires the expression of the transcription factor osterix (Osx), we investigated TNF effects on Osx. TNF inhibited Osx mRNA in pre-osteoblastic cells without affecting Osx mRNA half-life. Inhibition was independent of new protein synthesis. Analysis of the Osx promoter revealed two transcription start sites that direct the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
120
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(125 citation statements)
references
References 37 publications
(47 reference statements)
4
120
0
1
Order By: Relevance
“…However, endogenous osterix regulatory regions may contain additional AREs and other regulatory elements that have not been fully evaluated, and the AA stimulation of osterix expression in the time course experiments was based on the nucleosomal template in which the DNA is wrapped around histones. In addition, it is likely that the expression of other stage-specific transcription factors, such as Runx2, also contribute to full activation of the osterix gene during osteoblast differentiation (43)(44)(45). Some of these genes expressed in differentiated osteoblasts may also be regulated via ARE-dependent mechanisms, since putative AREs are present in the proximal promoter regions of Runx2.…”
Section: Discussionmentioning
confidence: 99%
“…However, endogenous osterix regulatory regions may contain additional AREs and other regulatory elements that have not been fully evaluated, and the AA stimulation of osterix expression in the time course experiments was based on the nucleosomal template in which the DNA is wrapped around histones. In addition, it is likely that the expression of other stage-specific transcription factors, such as Runx2, also contribute to full activation of the osterix gene during osteoblast differentiation (43)(44)(45). Some of these genes expressed in differentiated osteoblasts may also be regulated via ARE-dependent mechanisms, since putative AREs are present in the proximal promoter regions of Runx2.…”
Section: Discussionmentioning
confidence: 99%
“…Yamazaki et al [43] further demonstrated that p65 can interact with the Smad1-Smad5 complex in the nucleus and disrupt its binding to target promoters. Interestingly, TNFα-mediated inhibition of Runx2 was NF-κB dependent [41], but inhibition of Osx, a downstream target of Runx, was shown to be independent of NF-κB [44]. Overall, classical NF-κB activation downregulates OB differentiation (Figure 3).…”
Section: Nf-κb In Obsmentioning
confidence: 99%
“…Ascorbic acid and 1,25 (OH) 2 vitamin D 3 , which have positive roles in osteoblast function, have also been shown to up-regulate Osx expression (Maehata et al 2006, Xing et al 2007. Negative regulators of osteoblastogenesis, such as tumor necrosis factor-a (TNF-a) and p53, can inhibit Osx expression (Lu et al 2006, Wang et al 2006a,b, Zambetti et al 2006.…”
Section: Introductionmentioning
confidence: 99%